Tantangan dan Peluang Integrasi Kecerdasan Buatan Generatif dalam Praktik Manajemen SDM - Grace Yulianti; Benardi Benardi; Seger Santoso (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study is a qualitative literature review aimed at exploring the challenges and opportunities of integrating generative artificial intelligence (GAI) in human resource management (HRM) practices. GAI, as an advanced technology, holds significant potential to enhance operational efficiency in HRM through the automation of administrative tasks, improved accuracy in performance evaluations, and the development of more interactive and adaptive employee training. However, its implementation also faces several challenges, including employee resistance to change and the unpreparedness of technological infrastructure. Furthermore, ethical issues such as algorithmic bias in recruitment processes are a major concern, potentially exacerbating inequities if not properly monitored. This research identifies that the success of integrating GAI into HRM depends on the organization’s readiness to address technological and ethical challenges, as well as the importance of careful planning. The findings provide valuable insights for organizations in designing effective strategies for GAI integration to improve performance and organizational dynamics while addressing potential risks.